Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
♪Answer :
- g(n) = f(n)
»f(n) = 2n² + 6
so, g(n) = 2n² + 6
»g(2) = 2(2)² + 6
»g(2) = 2(4) + 6
»g(2) = 8 + 6
»g(2) = 14✅
- f(2)=2(2)^2+6=2(4)+6=8+6=14
As
[tex]\\ \rm\Rrightarrow g(n)=f(n)[/tex]
[tex]\\ \rm\Rrightarrow g(2)=f(2)=14[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.